Can Pakistan have creative cities? An agent based modeling approach with preliminary application to Karachi - Malik, Ammar A.; Crooks, Andrew T.; Root, Hilton L. (International Food Policy Research Institute, 2013)
The form and function of many cities are increasingly marred by congestion, sprawl and socioeconomic segregation, preventing them from experiencing expected productivity gains associated with urbanization. We operationalize these insights by creating a stylized agent-based model of a theoretical city, inspired by social complexity theory and the new urban literature.